FRI0188 Effectiveness of adalimumab combination therapy with methotrexate and non-methotrexate csdmards: results from the corrona rheumatoid arthritis registry. (15th June 2017) - Pappas, D; Griffith, J; Schlacher, CA; Suboticki, JL; Harrison, RW; Shan, Y; Karki, C; Kremer, JM
Abstract : Background: Combination therapy of methotrexate (MTX) with biologics results in superior outcomes vs. monotherapy. However, little is known on the effectiveness of adalimumab (ADA) combination therapy with non-MTX conventional synthetic disease modifying anti-rheumatic drugs (csDMARD). Objectives: To evaluate whether ADA in combination with non-MTX csDMARD has similar effectiveness as MTX combination therapy on clinical and patient report outcomes (PROs). Methods: Adult RA patients, naïve to other monoclonal antibodies, who initiated standard dose ADA (40mg q2w) in combination with MTX or ≥1 non-MTX csDMARD between 2003–2016 and had a 6 month follow-up visit were included. The primary outcomes were mean change in clinical disease activity index (CDAI) and mean change in PROs (mHAQ, pain, fatigue, morning stiffness) from baseline to 6 months. Secondary outcomes included achievement of remission (CDAI≤2.8)/low disease activity (LDA: CDAI≤10). Outcomes were evaluated adjusting for covariates that differed at the time of initiation using mixed model linear regression. Kaplan-Meier survival analysis was used to examine the persistency of ADA between the two groups. Results: A total of 754 patients were included: N=519 ADA+MTX and N=235 ADA+non-MTX csDMARD. Patients on ADA+MTX were slightly younger (mean age: 54.5 vs 57.4 years), with shorter disease duration (median: 3 vs 5 years), more likely to be biologic naïve (77% vs 69%) compared to patients on ADA+nonMTX csDMARD (all p<0.05). Disease activity and PROs were comparable in both groups at the time of initiation (mean CDAI: 20.4 vs 22.8; mean pain: 45.3 vs 45.9; mean fatigue: 46.3 vs 47.8; mean patient global assessment: 42.8 vs 42.9 (on a VAS 0–100) in ADA+MTX and ADA+nonMTX csDMARD group respectively. Adjusted analysis showed that patients on ADA+MTX had significantly lower mean CDAI at 6 months and higher change in CDAI vs patients in the ADA+non-MTX csDMARD group (p<0.05). In addition, patients on ADA+MTX were more likely to achieve LDA compared to the ADA+non-MTX csDMARD group (Table). Change in PROs and persistency of ADA was comparable in both groups. Conclusions: In this real world study, patients on ADA+MTX had significantly greater improvements in disease activity compared to patients on ADA+nonMTX csDMARD therapy but had comparable improvements in PROs at 6 months from initiation. Acknowledgements: This study is sponsored by Corrona, LLC. The Corrona, LLC. has been supported through contracted subscriptions in the last two years by AbbVie, Amgen, BMS, Crescendo, Eli Lilly and Company, Genentech, GSK, Horizon Pharma USA, Janssen, Momenta Pharmaceuticals, Novartis, Pfizer, Roche and UCB. The design, study conduct, and financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Disclosure of Interest: D. Pappas Grant/research support from: AbbVie, Consultant for: AbbVie, Employee of: Corrona, LLC, J. Griffith Shareholder of: AbbVie, Inc, Employee of: AbbVie, Inc, C. Schlacher Shareholder of: AbbVie, Inc, Employee of: AbbVie, Inc, J. Suboticki Shareholder of: AbbVie, Inc, Employee of: AbbVie, Inc, R. Harrison Employee of: Corrona, LLC, Y. Shan Employee of: Corrona, LLC, C. Karki Employee of: Corrona, LLC, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: AbbVie, Genentech, Lilly, Novartis, Pfizer, Consultant for: AbbVie, Amgen, BMS, Genentech, Lilly, Regeneron, Sanofi, Pfizer, Employee of: Corrona, LLC